Market anomalies in the Korean stock market - Minyeon Han; Dong-Hyun Lee; Hyoung Goo Kang (Journal of Derivatives and Quantitative Studies: Seonmul yeon'gu (JDQS), 2020)
This paper aims to replicate 148 anomalies and to examine whether the performance of the Korean market anomalies is statistically and economically significant. First, the authors observe that only 37.8% anomalies in the universe of the KOSPI and the KOSDAQ and value-weighted portfolios have t-statistics that exceed 1.96. When the authors impose a higher threshold (an absolute value of t-statistics of 2.78), only 27.7% of the 148 anomalies survive. Second, microcaps have large impacts. The results vary significantly depending on whether the sample included stocks in the KOSDAQ and whether value-weighted or equal-weighted portfolios are used. The results suggest that data mining explains large portion of abnormal returns. Any tactical asset allocation strategies based on market anomalies should be applied very cautiously.
Keywords: 330; Data mining; Anomaly; Factor; Microcap stocks; Tactical asset allocation